2010
DOI: 10.1007/s00221-010-2372-6
|View full text |Cite
|
Sign up to set email alerts
|

Movement chunking during sequence learning is a dopamine-dependant process: a study conducted in Parkinson’s disease

Abstract: Chunking of single movements into integrated sequences has been described during motor learning, and we have recently demonstrated that this process involves a dopamine-dependant mechanism in animal (Levesque et al. in Exp Brain Res 182:499-508, 2007; Tremblay et al. in Behav Brain Res 198:231-239, 2009). However, there is no such evidence in human. The aim of the present study was to assess this question in Parkinson's disease (PD), a neurological condition known for its dopamine depletion in the striatum. El… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
59
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 38 publications
6
59
0
Order By: Relevance
“…While the overlap between the neural correlates of chunking and WM gating (Graybiel 1998;Bor et al 2003;Gruber et al 2006;Tremblay et al 2010;Murty et al 2011;D'Ardenne et al 2012;Wymbs et al 2012;Jin et al 2014) was considered as indirect evidence of their possible interactions, in accordance with the computational models (O'Reilly and Frank 2006; Grossberg and Kazerounian 2011), we provide here, for the first time, behavioral evidence that chunking is linked to WM gating processes. This suggests that, in accordance with our prediction, chunking during sequence performance relies on the same mechanisms as in WM updating tasks, i.e., presumably the capacity to gate the access of information to WM while filtering irrelevant distractors (Gruber et al 2006;O'Reilly and Frank 2006;D'Ardenne et al 2012).…”
supporting
confidence: 85%
“…While the overlap between the neural correlates of chunking and WM gating (Graybiel 1998;Bor et al 2003;Gruber et al 2006;Tremblay et al 2010;Murty et al 2011;D'Ardenne et al 2012;Wymbs et al 2012;Jin et al 2014) was considered as indirect evidence of their possible interactions, in accordance with the computational models (O'Reilly and Frank 2006; Grossberg and Kazerounian 2011), we provide here, for the first time, behavioral evidence that chunking is linked to WM gating processes. This suggests that, in accordance with our prediction, chunking during sequence performance relies on the same mechanisms as in WM updating tasks, i.e., presumably the capacity to gate the access of information to WM while filtering irrelevant distractors (Gruber et al 2006;O'Reilly and Frank 2006;D'Ardenne et al 2012).…”
supporting
confidence: 85%
“…Among the other structures found activated in SRTT, it has been suggested that the BG are involved in the chunking process as demonstrated in both animals (Levesque et al, 2007;Jog, Kubota, Connolly, Hillegaart, & Graybiel, 1999;Aldridge & Berridge, 1998;Graybiel, 1998;Cromwell & Berridge, 1996;Berridge & Whishaw, 1992) and humans (Tremblay et al, 2010;Boyd et al, 2009). A similar assumption has been made for the hippocampus, because its lesion impairs associative learning in SRTT (Curran, 1997), a finding confirmed in rodents (Ergorul & Eichenbaum, 2006).…”
Section: Discussionmentioning
confidence: 83%
“…This manipulation does not interfere with well-learned sequences, but disrupts the formation of new chunks (Levesque et al 2007). Chronic dopamine denervation in patients with Parkinson's disease can also lead to an impairment of chunking for new sequences of movement (Tremblay et al 2010). There is also emerging evidence from human neuroimaging that the strength of activity in the associative striatum varies on a trial-by-trial basis with the degree to which subjects put together elements of motor sequences into chunks, the concatenation aspect of chunking (Wymbs et al 2012).…”
Section: From Bracketing To Chunks: Shaping the Elements Of Action Inmentioning
confidence: 99%